Le contrat de placement de fonds : une valeur mobilière envahissante - Antaki, Nabil (Les Cahiers de droit, 1978)
This essay defines the concept of « investment contract » as used in the securities acts. It analyses the classical Howey test and the more recent « risk capital » approach as formulated by Sobieski and Hawaï Market. It is suggested that Howey consisted originally of the well-known, ever repeated classical test, and of an alternative approach based on risk. This last important element of Howey was mistakenly dropped by the Courts. It is submitted that the Howey test, regenerated and liberally applied, is dynamic and well adapted to cover all possible situations and precludes the necessity of a different definition. U.S. Courts increasingly use the « investment contract » concept as afar-reaching catchall definition. It is further submitted that the Canadian Courts, encouraged by the Supreme Court's decision in Pacific Coast Coin Exchange of Canada, might use the concept even more comprehensively than their American counterparts.